2015
DOI: 10.5942/jawwa.2015.107.0078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Modified Inlets on Residence Times in Baffled Tanks

Abstract: Sharp inlets, although prevalent, tend to reduce mixing efficiency in hydraulic contact tanks by affecting fluid and scalar transport throughout the entire system. Superior inlets are often not an option because of the prohibitive cost of upgrading preexisting tanks. To remedy this, seven inexpensive yet easily implemented attachments to a sharp inlet were tested on a full‐scale, baffled, prototypical contact tank. Cumulative residence time distributions of a conservative, passive scalar were obtained for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nasyrlayev et al [25] investigated the effects of implementing perforated baffles to improve the mixing in disinfection tanks and reported reduction in dead zones in each compartment of the baffled contact tank. Carlston et al [26] investigated the impact of inlet flow conditions and geometrical shapes on the hydraulic retention time of baffled tanks and highlighted the positive impact of tee-attachment installation at the inlet on retention time and hydraulic efficiency of contact tanks. Zhang et al [27] successfully developed a numerical model for evaluating the efficiency of ozone contact tanks and concluded that fluctuations in seasonal flow rate has a significant impact on the performance of ozone disinfectant contact tanks.…”
Section: Introductionmentioning
confidence: 99%
“…Nasyrlayev et al [25] investigated the effects of implementing perforated baffles to improve the mixing in disinfection tanks and reported reduction in dead zones in each compartment of the baffled contact tank. Carlston et al [26] investigated the impact of inlet flow conditions and geometrical shapes on the hydraulic retention time of baffled tanks and highlighted the positive impact of tee-attachment installation at the inlet on retention time and hydraulic efficiency of contact tanks. Zhang et al [27] successfully developed a numerical model for evaluating the efficiency of ozone contact tanks and concluded that fluctuations in seasonal flow rate has a significant impact on the performance of ozone disinfectant contact tanks.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended the consideration of this variability in the operation of a WTP. Carlston and Venayagamoorthy [14] conducted experimental and numerical studies on a full-scale baffled contact tank with three chambers. Various inlet configurations were tested and it was found that the mixing efficiency could be enhanced with the implementation of a horizontal tee attachment at the inlet.…”
Section: Introductionmentioning
confidence: 99%
“…Research presented in this article not only highlights the importance of a well‐designed inlet but also investigates the application of local modifications for improving poorly designed contact tanks. Random industrial packing material served as the investigated system modifier for this study, but other modifications such as inlet diffusers, tees, or perforated baffles have the potential to provide similar benefits (e.g., Carlston & Venayagamoorthy 2015, Greene et al 2006). Packing material is traditionally used in vapor separation towers to facilitate the stripping of volatile organic compounds from contaminated liquids, but it has also been applied in wastewater treatment applications, such as trickling filters, where it is used to facilitate biofilm growth (Pilling & Holden 2009, USDOE 2001, Richards & Rienhart 1986, Kavanaugh & Trussell 1980).…”
mentioning
confidence: 99%